Penelitian-Penelitian Dari Ranah Teknik Untuk Meningkatkan Kualitas Sumber Daya Manusia melalui Inovasi Penelitian dan Pengabdian kepada Masyarakat - Rahadian Zainul (Prosiding, 2023)
It is hoped that increasing economic growth can be directed at increasing public income and meeting daily needs. The aim of this research is to determine the influence of service quality variables (X1), price (X2), and promotion (X3) on purchasing decisions at PT Asia Paramita Indah Batam (Y). In this research, the sampling process was carried out using a non-probability sampling method, namely a sampling technique that does not provide an equal opportunity to be selected into the sample. For sampling, the author used a saturated sampling method. Based on the sampling technique above, using a saturated sampling method from a total population of 135 people, 135 people were taken as a sample. Data was collected using a questionnaire which was measured using a Likert scale. This research uses multiple linear regression analysis with the help of the SPSS version 20.0 program. The results of this research show that the variables service quality (X1), price (X2), and promotion (X3) simultaneously influence purchasing decisions at PT Asia Paramita Indah Batam. The variables service quality (X1), price (X2), and promotion (X3) partially influence purchasing decisions at PT Asia Paramita Indah Batam.